2019
DOI: 10.12962/j20882033.v29i3.3690
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Aggregate Gradation to Improve The Characteristics of Geopolymer Based Asphalt Concrete

Abstract: The previous study showed that asphalt concrete using filler geopolymer generate a higher value of stability. On the other hand, the value of flow and the porosity of the asphalt concrete were out of the specification range. This study examines the aggregate gradation analysis to improve the characteristics of mixed asphalt concrete geopolymer. The gradation of aggregate is variated into three following the available specification. The range of specification is then separated into three; those are aggregate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The study results indicated that the medium gradation produces the optimum characteristics with enhanced stability value and slightly increase voids of the mixture [40]. From previous researchers, it can be concluded that the use of geopolymer as a filler substitute can improve the Marshall and mechanical properties for asphalt concrete mixtures.…”
Section: Fillermentioning
confidence: 77%
See 1 more Smart Citation
“…The study results indicated that the medium gradation produces the optimum characteristics with enhanced stability value and slightly increase voids of the mixture [40]. From previous researchers, it can be concluded that the use of geopolymer as a filler substitute can improve the Marshall and mechanical properties for asphalt concrete mixtures.…”
Section: Fillermentioning
confidence: 77%
“…Though, all the values obtained were within the stipulated standard for asphalt concrete mixtures. Also, a study by Aditama et al [40] using filler geopolymer made from fly ash investigates the aggregate gradation assessment to enhance the characteristics of mixed asphalt concrete geopolymers. The aggregate requirement set was divided into three; upper, middle, and lower limits.…”
Section: Fillermentioning
confidence: 99%